Anticultism in France: Scientology, religious freedom, and the future of new and minority religions - Westbrook, Donald A. (Cambridge elements. Elements in new religious movements, 2024)
This Element introduces readers to the problem of anticultism and antireligious movements in France. The first section offers an overview of anticultism in France, including the paradoxical place of modern French secularism (laïcité) that has shaped a culture prejudiced against minority religions and new religions (sectes or 'cults') and impacted Europe more broadly. This includes state-sponsored expressions, in particular MIVILUDES, an organization funded by the French government to monitor cultic or sectarian deviances. The second section takes up the case of the American-born Church of Scientology, tracing its history in the country since the late 1950s and how it has become a major focus of anticultists in France. The Element concludes with reflections on the future of new and minority religions in France. A timeline provides major dates in the history of anticultism in modern French history, with a focus on items of relevance to Scientology in France.